Effectiveness of combined Malaysia healthy plate method (half-half quarter) and physical activity intervention at workplace setting among healthcare workers - Sreevali Muthuvadivelu; Narwani Hussin; Prema Muninathan; Low, Phei Keow; Nancy Anne Josop; Ahmad Mu’alzaffardan Putra Bin Kamaruddin; Noor Hayati; Kogilavani (Penerbit Universiti Kebangsaan Malaysia, 2023)
Introduction; Overweight and obesity are becoming a major health issue which contributes to the increase in morbidity and mortality. This study aimed to evaluate the effect of the diet intervention and exercise for weight reduction among obese but healthy adults. Methods; This was a quasi-experimental study using designed Structured Diet with Program adapted from Malaysia Healthy Plate method (half-half quarter) with physical exercise for weight reduction. The anthropometry and biochemistry parameters were monitored and collected pre- and post-program. The body mass index (BMI) cut off points by World Health Organization (WHO) for Asian population was used to define obesity in this study. Results; 30 healthcare workers (HCWs) were recruited. However, only 27 HCWs completed the program. The pre- and post-program mean BMI was 32.90 kg/m2 and 31.39 kg/m2 and weight was 81.25 kg to 77.37 kg. The total cholesterol reduced significantly with mean 5.65 mmol/l to 5.34 mmol/l. Other blood parameters showed some reduction but not statically significant with mean Fasting Blood Sugar (FBS): 4.82mmol/l to 4.69mmol/l, mean High Density Lipoprotein (HDL): 1.43mmol/l to 1.32mmol/l mean Low Density Lipoprotein (LDL): 3.54mmol/l to 3.42mmol/l and mean TG 1.52mmol/l to 1.31mmol/l. Conclusions; Overall, the programme led to a considerable reduction in body weight, BMI, and total cholesterol. Even though other blood parameters did not show statistically significant reduction but they still showed some reduction in postprogramme. This method was recommended to be implemented among Malaysians for longer duration to achieve significant reduction in blood parameters. However, the commitment and motivation of the HCWs were highly needed to ensure the effectiveness and adherence to the diet method.